Theoretical implications of cellular immune reactions against helper lymphocytes infected by an immune system retrovirus. - Reibnegger, G (1987)
The breakdown of the immune system induced by the human immunodeficiency virus might be due to the active immune destruction of human immunodeficiency virus-infected helper T lymphocytes expressing viral antigens. By numerical simulation, we have studied possible consequences that a hypothetical immunodeficiency virus (IDV) may have on the cellular immune response by using a mathematical model. In this model, IDV infects CD4+ (helper) T cells and is actively synthesized by the immunologically activated helper T cells. Infected helper T cells synthesizing IDV express antigenic determinants specific for IDV and trigger a cellular immune response against themselves that is mediated by cytotoxic T cells and cytotoxic macrophages. The dynamic evolution of the model in the case of mixed-type infections with IDV and with another pathogen that evokes a cell-mediated immune response shows strong interactions between both simultaneous infections. The model might be of value to elucidate the dynamics leading to opportunistic infections. Furthermore, a pivotal role for immunological stimulation in the progressive exacerbation of the disease can be demonstrated.